Kegiatan Edukasi Literasi Media Sosial bagi Generasi Muda: Upaya Mendorong Penggunaan Media Sosial yang Bijak di TPQ Al Hidayah, Pacar Kembang, Surabaya - Landeva Kharisma Al Azmi (PT. Adriani Mandiri Publisher, 2026)
The rapid development of digital technology has contributed to the growing use of social media among the younger generation. However, when not used appropriately, social media can give rise to various issues, including the spread of misinformation, cyberbullying, and internet misuse. Therefore, improving social media literacy is crucial to enable the younger generation to use media more effectively and intelligently. The purpose of this community service program is to teach social media literacy to the younger generation at the Al Hidayah Pacar Kembang Islamic Boarding School (TPQ). The method used is a descriptive approach using Asset-Based Community Development (ABCD). Activities include preparation, material delivery, discussion, and answer sessions. Results indicate that participants demonstrated high levels of motivation throughout the program and significantly improved their understanding of social media use. Participants also understood the importance of ethics when interacting online and were able to recognize the positive and negative impacts of social media use. Therefore, this educational activity can be a way to increase the capacity of the younger generation to use social media in a more constructive and productive manner